NEW DATA ON THE AGE OF THE DIABASES AND ROCK SALT OF THE SEREGOVO SALT DOME - Yushkin N.P. (My University, 1990)
The presence of igneous rocks of mafic composition (diabases and dolerites) in the caprock of the Seregovo salt dome, about 75 km north of Syktyvkar, in a platform region with a large area of Mesozoic-Cenozoic sedimentary cover (the boundary of the Sysol swell and the Vychegodskiy downwrap on the north of the Russian Plate), where not even the slightest signs of igneous activity had previously been known, is an astonishing geological fact and fully merits investigation. The nature of the diabases is the key to understanding the dome, and we therefore analyzed the available data and made additional investigations on a core collected from commercial well. The data indicate that the primary salt constituting the Seregovo salt dome dome is late is late Proterozoic. This is confirmed by data from reference wells in the region, which indicate the presence of an evaporite environment in Vendian-Cambrian time, and by seismic data which indicate that Upper Proterozoic salts occur over a wide area.
Keywords: Vendian; Cambrian; Proterozoic; Cenozoic; Mesozoic; Кайнозой; Cenozoic; Mesozoic; Precambrian::Proterozoic; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Мезозой; Палеозой::Кембрийская; Докембрий::Протерозой; Докембрий::Протерозой::Неопротерозойская::Вендский